Pengaruh Penerapan Kurikulum Merdeka Terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X SMA Negeri I Titehena - Reinaldis Masi (Science and Education Journal (SICEDU), 2026)
This research aims to determine the effect of implementing the independent curriculum on student learning outcomes in the economics subject of class X of SMA Negeri 1 Titehena. This research uses a descriptive quantitative research method that describes the variables as they are, supported by data in the form of numbers generated from actual conditions The population and sample used in this study were 41 students of class X of SMA Negeri I Titehena, with the sampling technique used being the saturated sampling technique or census technique. The data collection technique used was a questionnaire distributed to all respondents. Data analysis techniques using simple linear regression analysis. The results of the research and data analysis show that the independent curriculum variable has a significant effect on student learning outcomes in the economics subject of class X of SMA Negeri I Titehena, as indicated by the results of the t-test with a calculated t value > t table (7.298 > 1.684) with a significance level of 0.00 < 0.05.These results show that the independent curriculum has an impact on learning outcomes in the economics subject of class X students of SMA Negeri 1 Titehena.